2021
DOI: 10.1161/str.52.suppl_1.14
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 14: Global Impact of the Covid-19 Pandemic on Subarachnoid Hemorrhage

Abstract: Introduction: During the COVID-19 pandemic, decreased volumes of stroke admissions and mechanical thrombectomy were reported. The objective was to examine whether subarachnoid hemorrhage(SAH) hospitalizations and ruptured aneurysm coiling interventions demonstrated similar declines. Methods: We conducted a global, retrospective, observational study across 6 continents, 37 countries, and 140 comprehensive stroke centers. Patients with diagnosis of SAH, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In our study, we observed a decrease in cases of aneurysmal SAH during the first wave of the COVID-19 pandemic (March-October 2020) compared to the 2019 period (49 vs. 65 cases). ese findings are similar to those reported by several authors, such as Nguyen et al, [20] Nogueira et al, [22] and Bernat et al, [5] among others, [4,13,15,26] who found a decline in admissions for acute ischemic and hemorrhagic cerebrovascular diseases during the 1 st months of the pandemic in different countries worldwide. is decline was more evident in hospitals that received a high number of patients infected with COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we observed a decrease in cases of aneurysmal SAH during the first wave of the COVID-19 pandemic (March-October 2020) compared to the 2019 period (49 vs. 65 cases). ese findings are similar to those reported by several authors, such as Nguyen et al, [20] Nogueira et al, [22] and Bernat et al, [5] among others, [4,13,15,26] who found a decline in admissions for acute ischemic and hemorrhagic cerebrovascular diseases during the 1 st months of the pandemic in different countries worldwide. is decline was more evident in hospitals that received a high number of patients infected with COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…There was a total of 345 COVID-SAH cases reported in the international literature at the time of analysis. This may be underreported, when considering the global decrease in admissions for SAH during the pandemic, attributable to an avoidance in seeking medical care owing to fear of contracting COVID-19 23 , 35 . Whilst most (94.2%) of the COVID-SAH cases were reported in the US, this does not reflect the geographical incidence of SAH, known to be highest in Finland and Japan 16 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…[11] Clinically, ischemic stroke is frequently reported, and management criteria are urgently needed in the US. [7] e risk of developing SAH is currently unknown and considered controversial; [12] however, it is associated with prolonged hospitalization and a poor prognosis. [14] ere are scattered reports of arterial dissection, including ruptured VA dissecting aneurysms.…”
Section: Discussionmentioning
confidence: 99%